Technology as a facilitator of change : a case study of paper to paperless. - Hundermark, Michael John (My University, 2011)
A South African insurance company has embarked on the process of converting the paper which makes up its claim files to digital images in all of its national branches. The removal of paper from this environment could leave a trail of mass destruction in terms of the loss in business production and the damage caused to its already fragile employees; not to mention the loss of potential business as a result of poor customer service during this change. The researcher was commissioned to facilitate the training of the software system which is being used to manage the digital images that replaced the old paper claim files. The purpose of this study was to understand the impact of using an interactive compact disk (CD) as a training instrument on the claims clerks and to gauge whether the business could recover faster than what current research suggests during planned change events by using this technology as a training tool. The paperless system was piloted at the largest insurance branch which formed the research site of this ethnographic case study. The researcher entrenched himself at this site and collected data over a period of 18 months. The CD impacted the claims clerks by assisting them to cope with typical symptoms of change through its carefully planned design, which took cognisance of the pedagogical needs of adults during their learning by blending various learning theory with different multimedia. The research also showed a period of recovery in terms of the productivity of claims processing from the time of the implementation of the paperless system. Although it cannot be conclusively proven that the processing of claims recovered sooner than what research shows, it does create a benchmark for future such cases to use during their paper-topaperless change events.